Use of medicinal plants by community from Fazenda Nova district, Brejo da Madre de Deus, PE, Brazil - Lila Messerschmidt; Rafaela Alves Pereira da Silva; Maria Rita Cabral Sales de Melo (Universidade Estadual de Alagoas, 2023)
The survey of medicinal plants used by people in the Fazenda Nova district, Brejo da Madre de Deus Municipality, Pernambuco State, Brazil was the main aim of this work. Data collection was conducted through semi-structured interviews. The botanical material was identified and incorporated at the Herbarium Professor Vasconcelos Sobrinho (PEUFR) of the Universidade Federal Rural de Pernambuco. 79 species were recorded, distributed in 40 families. The most representative families were: Fabaceae (14 ssp.), Lamiaceae (7 ssp.), Euphorbiaceae (6 ssp.), Asteraceae (3 ssp.), Bignoniaceae (3 ssp.) and Solanaceae (3 ssp.), the most cited therapeutic indications were for treating respiratory problems (24.54%), gastrointestinal disorders (17.47%) and inflammation in general (11.52%) . The tea was the main form of preparation and the leafs were the part of the plant most used in the production of natural remedies. The species of Angico (Anadenanthera macrocarpa (Benth.) Brenan., Aroeira (Astronium urundeuva (M.Allemão) Engl.), Babosa (Aloe vera L.  Burm. f.), Colônia (Alpinia zerumbet (Pers.) Burtt. R. M. Sm), Hortelã-miúda (Mentha crispa L.) and  Romã (Punica granatum L.) stood out because, besides being mentioned by all of the informants, there was complete consensus regarding the main use of the plants, reaching the ROP 100.